Statistical Sensitivity Required to Detect Any Potential Difference of Bioavailability Between DL-Methionine and DL-Methionine Hydroxy Analogue in Layers - Liu, Z.; Bateman, A.; Sohail, S.S.; Zinner, B.; Roland Sr., D.A. (International Journal of Poultry Science, 2004)
Two studies were conducted to compare bioavailability of DL-methionine hydroxy analogue-free acid (MHA-FA) relative to DL-methionine (DLM) in layers. The bioavailability was compared for egg production, egg mass, egg weight and feed conversion. In trial 1 five supplemental levels of methionine (0.02, 0.04, 0.06, 0.08 and 0.10%) from DLM or MHA-FA source were added respectively to a basal diet containing 14.97% protein, 0.27% methionine, and 0.24% cystine. Hy-Line W-36 hens (1,760) 37 weeks old were used. Egg production was not improved beyond the first 0.02% added methionine level. Thus, an accurate bioavailability value of MHA-FA relative to DLM could not be obtained, indicating that this test was not statistically sensitive enough to estimate the bioavailability of MHA-FA relative to DLM. In trial 2, 1,920 Hy-Line W-36 hens 53 weeks old were used in a 3 x 2 x 2 factorial experiment with three protein levels, two supplemental methionine levels, and two methionine sources. DLM and MHA-FA were compared at different protein and supplemental methionine levels on an equimolar basis. There were no differences (P > 0.05) between the 0.02% and 0.04% supplemental methionine level or between DLM and MHA-FA in egg production, egg mass, or feed conversion. Because no difference in egg production, egg mass and feed conversion between 0.02% and 0.04% methionine could be detected and that difference should be greater than the difference between DLM and MHA-FA, no potential differences between DLM and MHA-FA could be detected. There was a difference (P < 0.05) in egg weight between the two supplemental methionine levels. Although the average egg weight of hens fed DLM was not higher (P > 0.05) than that of hens fed MHA-FA, the difference was calculated to indicate that the bioavailability of MHA-FA might be 88.9% on a molar basis or 78.2% on a weight basis.